Sedentary time associates detrimentally and physical activity beneficially with metabolic flexibility in adults with metabolic syndrome - Garthwaite, Taru (American Physiological Society, 2025)
Metabolic flexibility (MetFlex) describes the ability to respond and adapt to changes in metabolic demand and substrate availability. The relationship between physical (in)activity and MetFlex is unclear. This study aimed to determine whether sedentary time, physical activity (PA), and cardiorespiratory fitness associate with MetFlex. Sedentary time, standing, and PA were measured with accelerometers for 4 weeks in 64 sedentary adults with metabolic syndrome [37 women, 27 men; 58.3 (SD 6.8) years]. Fitness (V̇o2max; mL·kg-1·min-1) was measured with graded maximal cycle ergometry. MetFlex was assessed with indirect calorimetry as the change in respiratory exchange ratio (ΔRER) from fasting to insulin stimulation with hyperinsulinemic-euglycemic clamp and from low-intensity to maximal exercise. Carbohydrate (CHOox) and fat oxidation (FATox) were calculated from respiratory gases. High sedentary time associated with higher fasting RER [β = 0.35 (95% confidence interval: 0.04, 0.67)], impaired insulin-stimulated MetFlex (ΔRER) [β=-0.41 (-0.72, -0.09)], and lower fasting FATox [β=-0.36 (-0.67, -0.04)]. Standing associated with lower fasting RER [β=-0.32 (-0.62, -0.02)]. Higher standing time and steps/day associated with higher fasting FATox [β = 0.31 (0.01, 0.61), and β = 0.26 (0.00, 0.53)]. Light-intensity and total PA associated with better insulin-stimulated MetFlex [β = 0.33 (0.05, 0.61)], and β = 0.33 (0.05, 0.60)]. Higher V̇o2max associated with higher CHOox during maximal exercise [β = 0.81 (0.62, 1.00)], as well as during insulin stimulation [β = 0.43 (0.13, 0.73)]. P values are less than 0.05 for all associations. Sedentary time and PA associate with MetFlex. Reducing sitting and increasing PA of even light intensity might aid in the prevention of metabolic diseases in risk populations through their potential effects on energy metabolism.NEW & NOTEWORTHY High accelerometer-assessed sedentary time associates with metabolic inflexibility measured during hyperinsulinemic-euglycemic clamp in adults with metabolic syndrome, and more light-intensity and total physical activity associate with more metabolic flexibility. Physical activity behaviors may thus play an important role in the regulation of fuel metabolism. This highlights the potential of reduced sedentary time and increased physical activity of any intensity to induce metabolic health benefits and help in disease prevention in risk populations.